2001
DOI: 10.1034/j.1399-3089.2001.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms mediate the rejection of porcine neurons and endothelial cells transplanted into the rat brain

Abstract: In order to investigate the early cellular responses mediating xenograft rejection in the brain, porcine aortic endothelial cells (PAEC) or porcine fetal mesencephalic neurons (PNEU) were transplanted into the striatum of LEW.1A rats. PAEC were detected with a specific anti-beta1 integrin antibody, and PNEU with an anti-porcine neurofilament antibody, or an antibody recognizing the NeuN antigen. PAEC grafts were massively infiltrated within 24 h by OX42-positive cells, which may correspond to polymorphonuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Xenotransplantation of porcine foetal neuroblasts to overcome striatal dopamine or GABA decreases in patients with Parkinson's or Huntington's disease, respectively, seems a viable alternative to allotransplantion of human foetal donor tissue, especially because the latter is complicated by both practical and ethical issues [55]. However, it has been shown that xenotransplantation induces a severe immune response leading to the graft rejection [35,36,55]. For example, foetal porcine xenoneuroblasts can trigger a severe lymphocyte response [35,36] which might be mitigated with co-transplantation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xenotransplantation of porcine foetal neuroblasts to overcome striatal dopamine or GABA decreases in patients with Parkinson's or Huntington's disease, respectively, seems a viable alternative to allotransplantion of human foetal donor tissue, especially because the latter is complicated by both practical and ethical issues [55]. However, it has been shown that xenotransplantation induces a severe immune response leading to the graft rejection [35,36,55]. For example, foetal porcine xenoneuroblasts can trigger a severe lymphocyte response [35,36] which might be mitigated with co-transplantation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that xenotransplantation induces a severe immune response leading to the graft rejection [35,36,55]. For example, foetal porcine xenoneuroblasts can trigger a severe lymphocyte response [35,36] which might be mitigated with co-transplantation of MSCs. Therefore, MSCs, as being hypoimmunogenic, could increase graft survival without the use of immunosupressors when co-transplanted with pig brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to information about grafted cells, MRI can provide information about the surrounding tissue (i.e., lesion size, edema or inflammation), which may have an effect on graft survival or the functional recovery of the tissue. [27][28][29][30] …”
Section: Cellular Imagingmentioning
confidence: 99%
“…The cryopreservation mevide further evidence of cellular mechanisms playing an dium used was 0.9% saline, 0.6% glucose, and 10% diimportant role in the rejection of intracerebral xenotransmethyl sulfoxide (DMSO) (AIM-V medium, Gibco). plantation (13,39).…”
Section: +mentioning
confidence: 99%